Birds as Bioindicators: Revealing the Widespread Impact of Microplastics - Lara Carrasco; Eva Jiménez-Mora; Maria J. Utrilla; Inés Téllez Pizarro; Marina M. Reglero; Laura Rico-San Román; Barbara Martin-Maldonado (Birds)
The global crisis of plastic pollution, particularly involving microplastics (MPs) and nanoplastics (NPs), has profound ecological implications. Birds, serving as bioindicators, are especially susceptible to these pollutants. This systematic review synthesizes the current research on the presence, distribution, and impact of MPs and NPs on avian species, alongside advancements in detection methodologies. MPs and NPs have been identified in over 200 bird species across 46 families, encompassing several ecosystems, from Antarctica to Labrador, including Australia, China, and South Europe. Seabirds such as penguins, gulls, and shearwaters exhibit a high burden of MPs in tissues and feces due to fishing debris, while terrestrial species face contamination from urban and agricultural sources. Depending on their composition, MPs can cause gastrointestinal damage, oxidative stress, and bioaccumulation of toxic chemicals, particularly polyethylene and polypropylene. However, challenges in detection persist due to methodological inconsistencies, though advances in spectroscopy and flow cytometry offer improved accuracy. Addressing this pollution is vital for bird conservation and ecosystem health, requiring international collaboration and standardized research protocols.